MYTHONYM AND SPELLONYM IN UZBEKI AND ENGLISH FAIRY TALES (Scientific journal of the Fergana State University, 2024)
This article analyzes mythonyms and spellonyms used in Uzbek and English fairy tales, their origin and etymological characteristics.